2010
DOI: 10.1577/a09-085.1
|View full text |Cite
|
Sign up to set email alerts
|

Partial Replacement of Fish Meal with Soy Protein Concentrate in Diets of Atlantic Cod

Abstract: In two feeding trials conducted with juvenile Atlantic cod Gadus morhua (initial mean weight ¼ 87.9 or 15.92 g), soy protein concentrate (SPC) was used to replace fish meal in isonitrogenous, isocaloric diets. In the first trial, five experimental diets (47% protein, 15% fat; calculated gross energy ¼ 5,059 kcal/kg) were formulated to replace 28, 60, 80, and 100% of dietary fish meal. In the second trial, three diets were formulated with SPC to replace 0, 25, and 50% of the fish meal in a modified commercial d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 37 publications
2
26
0
Order By: Relevance
“…The final body weights, growth, condition factors, and SGRs of fish in the 100% FM replacement group, however, were lower than those receiving no or 50% FM replacement. Although completely replacing FM with SPC did not affect juvenile cod growth (Walker et al 2010), the present results are similar to those reported by Hansen et al (2007b) who showed lower growth rates in fish fed diets that had a high (75% or 100%) incorporation of less-refined plant proteins.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The final body weights, growth, condition factors, and SGRs of fish in the 100% FM replacement group, however, were lower than those receiving no or 50% FM replacement. Although completely replacing FM with SPC did not affect juvenile cod growth (Walker et al 2010), the present results are similar to those reported by Hansen et al (2007b) who showed lower growth rates in fish fed diets that had a high (75% or 100%) incorporation of less-refined plant proteins.…”
Section: Discussionsupporting
confidence: 90%
“…Histopathology.-Histological samples of proximal and distal intestine (n = 3/tank) were examined and scored as described by Walker et al (2010). Briefly, 2-mm sections were excised from 1 to 2 cm posterior to the pyloric caeca and from 1 to 2 cm anterior to the sphincter that delineates the distal chamber.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in yellowtail, growth and feed efficiency were reduced when FMP replacement by SBP was greater than 20% (Shimeno et al 1993). In contrast, juvenile red drum and Atlantic cod tolerated a replacement of FMP with SBP up to 50% (Reigh and Ellis 1992;Walker et al 2010).…”
Section: Discussionmentioning
confidence: 93%